Application of interdisciplinary connections and information technologies for development of motor skills in light athletic of girls - senior form pupils - Al-Ravashdeh, Abdel Baset; Kozina, Zh.L.; Kramskoy, S.I.; Bazilyuk, T.A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to work out and substantiate technologies of motor and intellectual aspects’ integral impact on process of training of light athletic’ throws and run techniques of 15-16 years old girls. Material: in the research 2 groups of pupils participated: control group (n = 22) and experimental group (n = 21). Results: Methodic of run, jumps and throws techniques’ training of senior school girl-pupils has been worked out. The methodic implies mastering of basic light athletic movements on the base of analogies with rational and economic movements in animate nature and laws of mechanic It conditions application of knowledge from physics, biology, mathematic for receiving of more complete understanding of light athletic movements’ correct technique. Conclusions: we have shown that application of interdisciplinary connections permits to make the process of movements’ training more effective in comparison with mastering material of purely physical education.